THE EFFECT OF A NATURAL EXTRACT-BASED EXPERIMENTAL BLEACHING GEL UPON THE COLOUR AND SURFACE ROUGHNESS OF A COMPOSITE RESIN - AN IN VITRO STUDY - MADA, Diana Carla; GASPARIK, Cristina; MOLDOVAN, Marioara; MIRON-BORZAN, Cristina Stefana; IRIMIE, Alexandra Iulia; CORNEA, Daniela; DUDEA, Diana; CÂMPIAN, Radu Septimiu (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Objective: To evaluate the bleaching effect and the changing in the surface roughness of one experimental natural-based bleaching gel and of three commercial bleaching gels, namely: Opalescence PF 16%, Ultradent, Opalescence Quick PF 45%, Ultradent (based on carbamide peroxide CP) and Philips Zoom DayWhite 6% HP light activated (based on hydrogen peroxide HP) upon A3 body shade Filtek Supreme, 3M Espe nanocomposite. Material and methods: Thirty disks of the A3 body shade Filtek Supreme, 3M Espe, were immersed in a coffee solution and further divided into 6 groups: group 1 was kept as control, while groups 2-6 underwent a certain bleaching protocol, with different materials and exposure time, as follows: group 2: experimental gel, five sessions, 6 hours each; group 3: Opalescence PF 16 % (Ultradent), five sessions 6 hours each; group 4: Opalescence Quick PF 45% (Ultradent), 2 sessions, 30 min each; group 5: Opalescence Quick PF 45% - 2 applications/30 min and Opalescence PF 16% - 5 applications/6h and group 6 was bleached using an in office gel containing HP 6% (Philips Zoom DayWhite 6% HP light-activated 2 applications/30min). CIE L*a*b* parameters and surface roughness were recorded before and after bleaching. Data were analyzed using one-way repeated measures ANOVA, and multiple comparisons were adjusted using the Bonferroni method (p<0.05). Results: The average colour differences at the end of the bleaching protocols were as follows: 1:ΔE*=1.40, 2:ΔE*=3.76, 3:ΔE*=5.13, 4:ΔE*=4.79, 5:ΔE*=5.44, and 6:ΔE*=6.83. Overall, a significant statistical difference was found between the groups (p<0.05). However, multiple comparisons showed no significant difference among the groups based on carbamide peroxide (CP) (3, 4, and 5) (p>0.05). The results of the statistical test indicated a significant effect of the bleaching gels only for groups 5 and 6 (p<0.05). For these groups, surface roughness significantly decreased after the bleaching protocol. For the experimental group, no significant modifications of the surface were observed. Conclusions: The most effective protocol was the in office bleaching method based on hydrogen peroxide (HP) with light activation. The natural extract-based gel was less efficient than CP and HP groups; however, ΔE* was above the acceptability threshold. The natural extract-based experimental bleaching gel showed no significant change upon surface roughness.